Strategi Pemasaran Beras Premium Berbasis Smart Farming: Mendorong Ketahanan Pangan dan Pemberdayaan Petani di Era Digital - Rizki Saputra; Tantri Yanuar Rahmat Syah; Edi Hamdi; Ketut Sunaryanto (Yayasan Literasi Sains Indonesia, 2025)
This community service activity aims to design an effective marketing strategy for premium rice producer PT Agro Panca Unggul (APU) by utilizing smart farming technology. This community service activity examines how the application of advanced technologies such as the Internet of Things (IoT), drones, precision sensors, and cloud-based data management systems can improve the productivity, quality, and efficiency of premium rice production. The method used is a descriptive study involving market analysis, consumer segmentation, and internal company evaluation. The results of the community service activity indicate that smart farming technology enables PT APU to produce premium rice with consistent high quality standards, reduce production costs through efficient use of resources, and support marketing decision-making based on real-time data. The proposed marketing strategy includes market segmentation focused on middle- to upper-class consumers in major cities, competitive premium pricing, intensive digital promotion, and product development that aligns with market preferences. This smart farming is expected to improve the quality of life of the community through access to premium rice and support broader food security. The target implementation of this smart farming is farmers who grow rice still using old methods. The community service activity identified key challenges such as the need for large capital investments and human resource adaptation to new technologies. In conclusion, the integration of smart farming technology in premium rice marketing planning provides a significant competitive advantage for PT APU, expanding market share and building a modern and sustainable brand image.